Experiments in exile : C.L.R. James, Hélio Oiticica, and the aesthetic sociality of blackness - Harris, Laura, 1967- (Commonalities., 2018)
Comparing the radical aesthetic and social experiments undertaken by two exile intellectuals, 'Experiments in Exile' charts a desire in their work to formulate alternative theories of citizenship, wherein common reception of popular cultural forms is linked to a potentially expanded, non-exclusive polity.